Activatable bispecific liposomes bearing fibroblast activation protein directed single chain fragment/Trastuzumab deliver encapsulated cargo into the nuclei of tumor cells and the tumor microenvironment simultaneously. (May 2017) - Tansi, Felista L.; Rüger, Ronny; Böhm, Claudia; Steiniger, Frank; Kontermann, Roland E.; Teichgraeber, Ulf K.; Fahr, Alfred; Hilger, Ingrid
Graphical abstract: Abstract: Molecular targeting plays a significant role in cancer diagnosis and therapy. However, the heterogeneity of tumors is a limiting obstacle for molecular targeting. Consequently, clinically approved drug delivery systems such as liposomes still rely on passive targeting to tumors, which does not address tumor heterogeneity. In this work, we therefore designed and elucidated the potentials of activatable bispecific targeted liposomes for simultaneous detection of fibroblast activation protein (FAP) and the human epidermal growth factor receptor 2 (HER2). The bispecific liposomes were encapsulated with fluorescence-quenched concentrations of the near-infrared fluorescent dye, DY-676-COOH, making them detectable solely post processing within target cells. The liposomes were endowed with a combination of single chain antibody fragments specific for FAP and HER2 respectively, or with the FAP single chain antibody fragment in combination with Trastuzumab, which is specific for HER2. The Trastuzumab based bispecific formulation, termed Bi-FAP/Tras-IL revealed delivery of the encapsulated dye into the nuclei of HER2 expressing cancer cells and caused cell death at significantly higher rates than the free Trastuzumab. Furthermore, fluorescence imaging and live microscopy of tumor models in mice substantiated the delivery of the encapsulated cargo into the nuclei of target tumor cells and tumor stromal fibroblasts. Hence, they convey potentials to address tumor plasticity, to improve targeted cancer therapy and reduce Trastuzumab resistance in the future. Statement of Significance: This work demonstrates the design of activatable bispecific liposomes aimed to target HER2, a poor prognosis tumor marker in many tumor types, and fibroblast activation protein (FAP), a universal tumor marker overexpressed on tumor fibroblasts and pericytes of almost all solid tumors. Encapsulating liposomes with a quenched concentration of a NIRF dye which only fluoresced after cellular degradation and activation enabled reliable visualization of the destination of the cargo in cells and animal studies. Conjugating single chain antibody fragments directed to FAP, together with Trastuzumab, a humanized monoclonal antibody for HER2 resulted in the activatable bispecific liposomes. In animal models of xenografted human breast tumors, the remarkable ability of the bispecific probes to simultaneously deliver the encapsulated dye into the nuclei of target tumor cells and tumor fibroblasts could be demonstrated. Hence, the bispecific probes represent model tools with high significance to address tumor heterogeneity and manage Trastuzumab resistance in the future.